Increased miR-203-3p and reduced miR-21-5p synergistically inhibit proliferation, migration, and invasion in esophageal cancer cells. Issue 1 (January 2019) - Xia, Yang; Wang, Yihui; Wang, Qi; Ghaffar, Maliha; Wang, Yuting; Sheng, Wang; Zhang, Fang
Abstract : Dysregulation of miR-203-3p and miR-21-5p has been identified in esophageal cancer (EC). The restoration of miR-203-3p and reduction of miR-21-5p were able to cause tumor suppression. Here, co-transfection of miR-203-3p mimics and miR-21-5p inhibitors led to an extraordinary increased expression of miR-203-3p and synergistically inhibited proliferation, migration, and invasion in EC cells. Moreover, we found that Ran GTPase ( Ran ) was dramatically inhibited in EC cells treated with the co-transfection of miR-203-3p mimics and miR-21-5p inhibitors. Finally, in-vivo studies showed that overexpression of miR-203-3p, combined with the suppression of miR-21-5p, significantly co-inhibited growth of tumors. The obtained data suggested that the development of miRNA-based combination therapeutics represents a promising cancer treatment strategy.